PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN DEEP LEARNING DI KELAS III SDN 04 SITIUNG DHARMASRAYA - Hadi Amelsi, Warisa; Desyandri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study's findings are influenced by learning activities that encourage students to participate actively. Aside from that, because the teaching process is very focused on the teacher, students are less involved in the learning process and less able to comprehend the material. Because of this, innovation in education is necessary to increase students' motivation and learning outcomes. The purpose of this study is to explain how the use of the Problem Based Learning (PBL) model in conjunction with the Deep Learning approach using Wordwall media in grade III SDN 04 Sitiung Dharmasraya enhances student learning outcomes in Pancasila education. Penelitian Tindakan Kelas (PTK) is a type of research that uses both quantitative and qualitative methods. Research is conducted in two stages, including perencanaan, pelaksanaan, pengamatan, and reflection as its components.Data collection techniques included observation, tests, and non-test methods. The research subjects consisted of the classroom teacher as the observer, the researcher as the practitioner, and 22 third-grade students as participants. The results showed improvements in all observed aspects. The average score of the teaching module increased from 85.72% in Cycle I to 96.43% in Cycle II. The teacher’s implementation aspect improved from 81.25% to 96.88%, while the student participation aspect increased from 79.69% to 93.75%. Students’ learning outcomes also improved from 68.81% in Cycle I to 85.15% in Cycle II. In conclusion, the implementation of the Problem Based Learning model with a Deep Learning approach assisted by Wordwall is effective in improving students’ learning outcomes in Pancasila Education in third-grade elementary school.